The ecology of large herbivores native to the coastal lowlands of the fynbos biome in the Western Cape, South Africa - Radloff, Frans Gustav Theodor (Stellenbosch : Stellenbosch University, 2008)
Thesis (DSc (Botany and Zoology))—-Stellenbosch University, 2008.